Gendered implications of the waves of COVID-19 and economic upgrading trajectories in digital value chains: Insights from Kenyan agricultural platforms - Aarti Krishnan; Monica Nganga; Timothy Foster (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2023)
Women play a critical yet under-researched role in global digital agri-food value chains, especially in smallholder production, which affects how they are able to economically upgrade (improve crop yields and product quality, and increase product diversification). Research suggests that women's participation in agricultural platform-driven value chains facilitates the overcoming of barriers such as access to productive resources and engenders upgrading. However, studies have shown mixed evidence of the benefits of ag-platforms, and there are very limited data on female farmers' contribution. Their economic upgrading possibilities are further compounded by the onset of shocks such as COVID-19. Predominantly only anecdotal evidence exists of how such shocks impact women in agriculture generally, let alone those using digital platforms. This paper seeks to answer the question: To what extent has the intensity of COVID-19 affected economic upgrading possibilities for women in platform-driven ag-value chains? The paper attempts to unpack economic upgrading through the different regimes of COVID-19, illustrating the dynamic effects experienced by women living through the shock. The paper uses a mixed methods approach, combining daily transaction data for over 3,000 farmers from 2019 to 2021 with 40 interviews of various value chain actors. The results show that women have been able to upgrade through the shock in terms of crop productivity and product quality more successfully than men, although there are differences across the different regimes of COVID-19; however, women have downgraded in terms of product diversification. The results are robust using pooled OLS, fixed effects, random effects, and seemingly unrelated regressions. The paper highlights a critical need to unpack shocks as a succession of regimes, rather than treating them as homogeneous entities, in order to provide a more holistic understanding of how women cope.
Keywords: O13; O19; D80; 330; digital; platforms; agriculture; gender; upgrading; value chains